2010
DOI: 10.4088/jcp.08m04754blu
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Anterior Cingulate and Orbitofrontal Volumes in Child Abuse–Related Complex PTSD

Abstract: In complex PTSD, not only the hippocampus and the ACC but also the OFC seem to be affected, even in the absence of comorbid borderline personality disorder. These results suggest that neural correlates of complex PTSD are more severe than those of classic PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
89
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(102 citation statements)
references
References 0 publications
11
89
1
1
Order By: Relevance
“…In conclusion, structural MRI studies sampling PTSD populations have observed gray matter differences in ACC (Thomaes et al, 2010) and hippocampal volumes (Woon et al, 2010). Our study extends these observations to include the PTSD-specific abnormalities in the cingulum, the white matter fiber that connects the ACC and hippocampus.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In conclusion, structural MRI studies sampling PTSD populations have observed gray matter differences in ACC (Thomaes et al, 2010) and hippocampal volumes (Woon et al, 2010). Our study extends these observations to include the PTSD-specific abnormalities in the cingulum, the white matter fiber that connects the ACC and hippocampus.…”
Section: Discussionsupporting
confidence: 74%
“…A majority of this research has revealed structural differences in gray matter, with smaller cortical volumes frequently associated with a PTSD diagnosis (Karl et al, 2006;Tavanti et al, 2012). Volumetric differences between PTSD and psychopathology-free controls (measured through MRI) have been largely observed in specific structures, such as the anterior cingulate cortex (ACC) and orbitofrontal cortex (Thomaes et al, 2010); however, between-group differences have been particularly apparent for the hippocampus, a brain region that is especially sensitive to the effects of chronic stress (for a review, see Woon et al, 2010). Not surprisingly, hippocampal abnormalities have been linked to cognitive and affective disruptions that characterize PTSD (Bremner, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Smaller hippocampal volume (partially) mediated the effect of CM on adolescent depression during a 5-year follow-up (Rao et al, 2010) and behavioural problems in children (Hanson, Nacewicz, et al, 2015). Larger hippocampal volumes, on the other hand, have been related to CM in healthy samples, suggesting a possible marker of resilient functioning (Mehta et al, 2009;Morey et al, 2016;Thomaes et al, 2010;Nim Tottenham et al, 2010;. Indeed, CM was not related with hippocampal volume reductions in resilient adults (i.e.…”
Section: Brain Structurementioning
confidence: 99%
“…Some structural and functional imaging studies report intriguing brain alterations associated with a history of child abuse including but not limited to the anterior cingulate and midcingulate cortices [23][24][25]. It is surprising, therefore, that no efforts have been made to reverse translate key issues into an experimental animal model.…”
Section: Human Imagingmentioning
confidence: 99%